Safety and feasibility of trans‐venous cardiac device extraction using conscious sedation alone—Implications for the post‐COVID‐19 era - Thomas Lachlan (Wiley, 2021)
Abstract Background Transvenous lead extraction (TLE) for implantable cardiac‐devices is traditionally performed under general anesthesia (GA). This can lead to greater risk of exposure to COVID‐19, longer recovery‐times and increased procedural‐costs. We report the feasibility/safety of TLE using conscious‐sedation alone with immediate GA/cardiac‐surgery back‐up if needed. Methods Retrospective case‐series of consecutive TLEs performed using conscious‐sedation alone between March 2016 and December 2019. All were performed in the electrophysiology‐laboratory using intravenous Fentanyl, Midazolam/Diazepam with a stepwise approach using locking‐stylets/cutting‐sheaths, including mechanical‐sheaths. Baseline patient‐characteristics, procedural‐details and TLE outcomes (including procedure‐related complications/death) were recorded. Results A total of 130 leads were targeted in 54 patients, mean age ± SD 74.6 ± 11.8years, 47(87%) males; dual‐chamber pacemakers (n = 26; 48%), cardiac resynchronization therapy‐defibrillators (n = 17; 31%) and defibrillators (n = 8; 15%) were commonest extracted devices. Mean ± SD/median (range) lead‐dwell times were 11.0 ± 8.8/8.3 (0.3‐37) years, respectively. Extraction indications included systemic infection (n = 23; 43%) and lead/pulse‐generator erosion (n = 27; 50%); mean 2.1 ± 2.0 leads were removed per procedure/mean procedure‐time was 100 ± 54 min. Local anesthetic (LA) was used for all (mean‐dose: 33 ± 8 ml 1% lidocaine), IV drug‐doses used (mean ± SD) were: midazolam: 3.95 ± 2.44 mg, diazepam: 4.69 ± 0.89 mg and fentanyl: 57 ± 40 µg. Complete lead‐extraction was achieved in 110 (85%) leads, partial lead‐extraction (<4 cm‐fragment remaining) in 5 (4%) leads. Sedation‐related hypotension requiring IV fluids occurred in 2 (managed without adverse‐consequences) and hypoxia requiring additional airway‐management in none. No procedural deaths occurred, one patient required emergency cardiac surgery for localized ventricular perforation, nine had minor complications (transient hypotension/bradycardia/pericardial effusion not requiring intervention). Conclusion TLE undertaken using LA/conscious‐sedation was safe/feasible in our series and associated with good clinical outcome/low procedural complications. Reduced risk of aerosolization of COVID‐19 and quicker patient recovery/reduced anesthetic risk are potential benefits that warrant further study.